Eksistensi Pendidik Sebagai Murobbi: Kajian Terhadap Peran Ganda Dalam Pendidikan Pesantren - Desyoni Advensia; Muthmainnah Choliq; Fatimatuzzahra Ade Sya’bani; Habibah Izza Hanasri (Advances In Education Journal, 2025)
Educators in Islamic boarding schools serve as key role models in shaping students’ character, such as noble values, cooperation, and social responsibility. This study aims to explore the dual role of these educators, both as academic teachers and as character mentors within the dormitory environment. This study employed a descriptive qualitative approach. Data were obtained through interviews with several teachers in a modern Islamic boarding school in East Java. In Islamic tradition, a teacher is not only a knowledge transmitter (mu'allim) but also a moral guide (murabbi). The dual role of educators includes: (1) teaching in classrooms (academic role), (2) supervising student discipline (guidance role), (3) accompanying religious activities (spiritual role), and (4) acting as dormitory caretakers (parental role). This research emphasizes that educators in Islamic boarding schools carry a dual responsibility. They are not only academic instructors but also key agents of character education. The study is expected to serve as a reference for future research on holistic education in Islamic boarding schools